AI 2041 : TEN VISIONS FOR OUR FUTURE - Lee, Kai-Fu; Qiufan, Chen (New York : Crown Currency, 2024)
A non-fiction author joins forces with a science-fiction novelist to blend imaginative storytelling and scientific forecasting to ask how artificial intelligence will change our world over the next 20 years
Includes index
Keywords: Artificial intelligence -- Forecasting